1984
DOI: 10.1247/csf.9.369
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in dorsal, ventral, animal and vegetal half-embryos of Xenopus laevis isolated at the 8-cell stage.

Abstract: ABSTRACT. Dorsal, ventral, animal and vegetal half-embryos of Xenopus laevis were isolated at the 8-cell stage, and their synthesis of protein examined during 12 h of culture. The kinetics of the uptake and incorporation of [35S]-methionine did not differ greatly among the four kinds of half-embryos. Two-dimensional gel electrophoreses showed that there were no detectable differences in the pattern of protein synthesis for the four types of half-embryos, at least during the first 6 h of culture which covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The nature and identities of these dorsal determinants are not currently well defined. Previous experiments have shown that these putative cytoplasmic factors may be mRNA or proteins ( Klein and King, 1988 , Miyata et al, 1987 , Shiokawa et al, 1984 ). Further, it has been argued that cytoplasmic polyadenylation may be the mechanism for the change in dorsal inducing activity of total RNA isolated from the dorsal lineage between the 8- and 16-cell stages ( Pandur et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nature and identities of these dorsal determinants are not currently well defined. Previous experiments have shown that these putative cytoplasmic factors may be mRNA or proteins ( Klein and King, 1988 , Miyata et al, 1987 , Shiokawa et al, 1984 ). Further, it has been argued that cytoplasmic polyadenylation may be the mechanism for the change in dorsal inducing activity of total RNA isolated from the dorsal lineage between the 8- and 16-cell stages ( Pandur et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular markers for neural differentiation, such as N-CAM (2,11,17) and homeobox-containing gene transcripts (4, 25), have been described. Richter and his colleagues also reported cDNA clones specific to neural differentiation (27). The qualitative and quantitative changes in keratin derivatives and their genes were also investigated in Xenopus (1,7,9,15,16,20).…”
Section: Introductionmentioning
confidence: 99%
“…University, Nagoya 453, Japan Department of General Education, Do170 trophoresis to analyze the changes of protein synthesis during early amphibian embryogenesis (3,27,29,30,31,32). But they were mainly involved in the analysis of animal-vegetal or dorsalventral polarity in Xenopus or in Ambystoma embryos.…”
Section: Introductionmentioning
confidence: 99%